Gli2 gene-environment interactions contribute to the etiological complexity of holoprosencephaly: evidence from a mouse model - Galen W. Heyne; Joshua L. Everson; Lydia J. Ansen-Wilson; Cal G. Melberg; Dustin M. Fink; Kia F. Parins; Padydeh Doroodchi; Caden M. Ulschmid; Robert J. Lipinski (The Company of Biologists, 2016)
Holoprosencephaly (HPE) is a common and severe human developmental abnormality marked by malformations of the forebrain and face. Although several genetic mutations have been linked to HPE, phenotypic outcomes range dramatically, and most cases cannot be attributed to a specific cause. Gene-environment interaction has been invoked as a premise to explain the etiological complexity of HPE, but identification of interacting factors has been extremely limited. Here, we demonstrate that mutations in Gli2, which encodes a Hedgehog pathway transcription factor, can cause or predispose to HPE depending upon gene dosage. On the C57BL/6J background, homozygous GLI2 loss of function results in the characteristic brain and facial features seen in severe human HPE, including midfacial hypoplasia, hypotelorism and medial forebrain deficiency with loss of ventral neurospecification. Although normally indistinguishable from wild-type littermates, we demonstrate that mice with single-allele Gli2 mutations exhibit increased penetrance and severity of HPE in response to low-dose teratogen exposure. This genetic predisposition is associated with a Gli2 dosage-dependent attenuation of Hedgehog ligand responsiveness at the cellular level. In addition to revealing a causative role for GLI2 in HPE genesis, these studies demonstrate a mechanism by which normally silent genetic and environmental factors can interact to produce severe outcomes. Taken together, these findings provide a framework for the understanding of the extreme phenotypic variability observed in humans carrying GLI2 mutations and a paradigm for reducing the incidence of this morbid birth defect.